Terapi Imunologi Pada Melanoma - Muhamad Addin Syakir; Dwi Indria Anggraini (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Introductions: Immunotherapy for cancer is used based on the principle of the disease that the immune system is able to produce an immune response to tumor cells. Treatment is currently available for selective melanoma patients based on the response rate of the disease. Objectives: To determine the management of melanoma using immunology. Methods: This article was compiled using the literature review method, using 32 sources derived from journals and books. Results: Interferon-? was approved for the treatment of adjuvant stage III melanoma with increased survival rate. New and more innovative approaches are needed with increasing therapeutic effects. The prognosis of patients with metastatic melanoma in the world has changed dramatically since the presence of an immune checkpoint inhibitor. Discussions: Ipilimumab, which targets the cytotoxic T lymphocyte-associated protein 4 (CTLA-4) protein is the first agent that exists. Furthermore, nivolumab and pembrolizumab that bind to programmed death protein 1 (PD-1) proteins have been shown to be more effective and lower in toxicity than ipilimumab. The combination of nivolumab or pembrolizumab with ipilimumab has resulted in increased response rates and patient survival rate results. This literature review will explore important clinical trial data that have led to the use of this immunotherapy agent in the world and some clinical trial results currently reported for new combination therapies. Conclusions: At present immunology therapy for melanoma management can be applied. Keywords: Chemotherapy, immunotherapy, management, melanoma